Analisis Kesesuaian Kawasan Mangrove sebagai Objek Daya Tarik Ekowisata di Desa Siahoni, Kabupaten Buru Utara Timur, Provinsi Maluku (Mangrove Suitability Analysis as an Object of Ecotourism Attraction in Siahoni Village, Buru Utara Timur Regency, Maluku Province) - Latupapua, Yosevita Theodora; Loppies, Ronny; Fara, Fitrah D.S. (Jurnal Sylva Lestari, 2019)
Most of the area in East Buru Utara Regency, Maluku Province are categorized as coastal lowlands, especially the Teluk Kayeli area. This area has the potential to be developed into a destination area for mangrove ecotourism destination due to its natural and preserved mangrove. The purpose of this study was to analyze the suitability of mangrove areas as an object of ecotourism attraction in Siahoni Village, Buru Utara Timur Regency, Maluku Province. The research approach is descriptive quantitative, using the survey method. Primary data including thickness, density, biota, and type of mangrove were collected through field observation at four observation stations, while secondary data including geographical condition, village monograph, and tide data were collected through literature study. Vegetation data were analyzed by measuring the relative density of each plant species and tourism suitability was analyzed by using tourism suitability index (TSI). Also, a SWOT analysis was also conducted to determine the strategy for developing mangrove ecotourism. Mangrove species observed in mangrove ecosystem at Teluk Kayeli, Siahoni Village consisted of Avicennia lanata, Sonneratia caseolaris, Bruguiera gymnorrhiza, Ceriops tagal, Nypa frutican, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Scyphyphora hydrophyllaceae, dan Xylocarpus granatum. The results showed that the TSI of mangroves at the observation station 1, 2, 3, and 4 were 65%, 72%, 72%, and 69%, respectively, and corresponded to the S2 category (suitable). Efforts to improve the suitability index of the mangrove area as an object of ecotourism attraction could be done through rehabilitation and reforestation, hence the environmental attraction and ecological function of the mangrove area could be improved. Keywords: ecotourism, Maluku, mangrove, tourism suitability index